Hukum Penyalahgunaan Foto Media Sosial Orang Lain Untuk Konten di Tinjau dari Fatwa MUI No 01 Tahun 2005 Tentang HKI (Studi Kasus Kreator Capcut Medan) - Fakar Arsyika, Mhd.; Rahman Harahap, Abd (UNES Law Review, 2023)
This research aims to analyze the legal implications of the misuse of photos from individuals' social media for content creation, focusing on the perspective of the Indonesian Council of Ulama (MUI) Fatwa No. 1 of 2005 on Intellectual Property Rights. A case study is conducted on Capcut creators in Medan as a representation of this phenomenon. The research methodology involves document analysis and interviews with several Capcut creators. this research, the author chose field research as the primary approach. This approach enables the researcher to approach respondents directly through interviews and observations. Interviews are defined as a verbal question-and-answer process between the researcher and respondents, conducted face-to-face to obtain direct information. In this context, the author conducted interviews with Capcut creators in the city of Medan. The findings indicate that the misuse of social media photos of others for content by Capcut creators in Medan may involve violations of intellectual property rights. MUI Fatwa No. 1 of 2005 provides legal guidance regarding the use of others' content; however, its implementation in the practices of Capcut creators still poses some issues.